T-Cell Receptor Gene Rearrangement Studies Using the GeneScan Technique as an Adjunct to the Histopathological Diagnosis of Mycosis Fungoides. (March 2015) - Ritz, Noa; Sahar, Dvora; Bergman, Reuven
Abstract : Abstract: T-cell receptor gene rearrangement studies are considered to be an adjunct to the histopathological diagnosis of mycosis fungoides (MF). Fluorophore-coupled primers in polymerase chain reactions followed by fragment analysis with a capillary electrophoresis device (GeneScan analysis) have been recently advocated and widely used. This study was performed to assess T-cell receptor γ-gene rearrangement GeneScan as an adjunct to the histopathological diagnosis of MF. We studied 163 cases. The rates of clonality using this technique were found to be 22/37 (59.5%) in early patch MF, 30/46 (65.2%) in more advanced stages, 13/34 (38.2%) in inconclusive cases, and 10/46 (21.7%) in benign inflammatory dermatoses. Our results support the histopathological criteria for the diagnosis of early patch MF, because of the close rates of clonality obtained in early patch MF with subtle histopathological findings, and in the more advanced subtypes of MF with more overt and specific histopathological criteria.